SIMULATION TRAINING: FEATURES OF TEACHING CLINICAL DISCIPLINES - Abdurakhimova Lola Anvarovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides data on the features of simulation training in the development of medical education. As well as the principles for the implementation of the simulation process, the main stages and features of teaching clinical subjects.